MEREKONSTRUKSI KISAH PEMBANGUNAN MENARA BABEL DARI PERSPEKTIF SPRITUALITAS KAUM PENTAKOSTAL - Kosma Manurung (Sekolah Tinggi Teologi Imauel Pacet, 2022)
The Bible that believers believe as a way of life tells many interesting stories to study and one of them is the story of the construction of the tower of Babel. This study specifically seeks to reconstruct the story of the construction of the tower of Babel from the perspective of the spirituality of the Pentecostals. By using text analysis methods and literature studies, the researcher attempts to systematically and deeply analyze the conditions of the times at that time, analyzing the passage of Genesis 11:1-9 regarding the construction of the tower of Babel in order to gain a comprehensive understanding to correlate with the perspective of the Pentecostals interpreting this story. . It is concluded that for the Pentecostals, the story of the construction of the Tower of Babel is interpreted as the limitation of human effort, misguided unity, it is necessary to prioritize the role of the Holy Spirit, and God's judgment.Alkitab yang diyakini orang percaya sebagai pedoman hidup menceritakan banyak kisah yang menarik untuk dikaji dan salah satunya adalah kisah pembangunan menara Babel. Penelitian ini secara khusus berupaya merekonstruksi kisah pembangunan menara Babel dari perspektif spritualitas kaum pentakostal. Dengan menggunakan metode analis teks dan kajian literatur, peneliti berupaya untuk menganalisa secara sistimatik dan mendalam kondisi zaman pada waktu itu, menganalisis perikop Kejadian 11:1-9 terkait pembangunan menara Babel ini guna mendapatkan pemahaman yang komprehensif untuk dikolerasikan dengan perspektif kaum pentakostal memaknai kisah ini. Disimpulkan bahwa bagi kaum pentakostal kisah pembangunan menara babel ini dimaknai sebagai keterbatasan usaha manusia, kesatuan yang salah sasaran, perlu mengedepankan peran Roh Kudus, dan penghakiman Tuhan.